Pathways to intercultural accuracy: Social projection processes and core cultural values. (13th June 2018) - Mor, Shira; Toma, Claudia; Schweinsberg, Martin; Ames, Daniel
Abstract: The present research examines intercultural accuracy—people's ability to make accurate judgments about outgroup values—and the role of social projection processes. Across four studies, U.S. and British participants showed low overall levels of intercultural accuracy for Chinese students' individualistic and collectivistic values. In line with recent changes toward individualism in China, we observed different levels of intercultural accuracy, hinging on whether the criterion values of Chinese were assessed before (2001) or after (2015) this shift. Important for the study of social projection, we observed that U.S./British participants projected their values onto the outgroup. Social projection tendency (measured in Study 2 and manipulated in Study 3) was associated with greater intercultural accuracy. The relationship between projection and accuracy also depended on the shifts in individualistic values of Chinese. Important for the study of intergroup relations, accuracy was positively associated with interest in future relationships with the Chinese.